2020
DOI: 10.1021/acs.jpcc.0c04645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of X-rays on Perovskite Solar Cells

Abstract: Synchrotron micro-and nanoprobe beamlines have demonstrated great potential to advance photovoltaic devices. Most importantly, their small X-ray spotsize has enabled the direct correlation of electrical performance with elemental composition at sub-grain resolution for a variety of polycrystalline solar cells. Whereas the bulk of most inorganic semiconductors is stable under the high X-ray flux of focused Xray beams, semiconductors with organic components are prone to a variety of degradation mechanisms. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
24
1
Order By: Relevance
“…40 After accounting for partial X-ray transmission through the nanometric perovskite film, the nano-focused X-ray irradiation is equivalent to ~700 suns, providing an accelerated test condition to monitor the stability and degradation of the perovskite crystal in the presence of a large concentration of carriers. 41 To analyze any structural degradation, a correlation coefficient of the diffraction pattern at each frame with respect to the initial one was calculated as a representation of structural degradation of perovskite, according to:…”
Section: Methodsmentioning
confidence: 99%
“…40 After accounting for partial X-ray transmission through the nanometric perovskite film, the nano-focused X-ray irradiation is equivalent to ~700 suns, providing an accelerated test condition to monitor the stability and degradation of the perovskite crystal in the presence of a large concentration of carriers. 41 To analyze any structural degradation, a correlation coefficient of the diffraction pattern at each frame with respect to the initial one was calculated as a representation of structural degradation of perovskite, according to:…”
Section: Methodsmentioning
confidence: 99%
“…XBIC: For XBIC measurements, requirements are relaxed as long as a chopper is used to modulate the X-ray beam. Dedicated XBIC scans could be performed more than an order of magnitude faster with comparable signal-to-noise; the long dwell time required for the multi-modal measurement would only be a drawback if X-ray beam-induced sample damage was present, as is the case, e.g., in perovskite solar cells [ 20 , 41 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…X-ray beam-induced current (XBIC): The absorption of an X-ray photon in the absorber layer of the solar cell leads to a particle shower of electrons and photons and, after thermalization, to multiple excited electron-hole pairs at the band edges (simulations of this process are detailed in the supplementary information (SI) of Reference [ 20 ]). Same as upon excitation by photons in the visible range, the electrons and holes can be separated within the solar cell and collected at the solar-cell contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Stuckelberger et al carried out nano-XRF with X-ray beam-induced current (XBIC) on mesoscopic MAPbI 3 solar cells. The combined XRF/XBIC measurements give valuable correlation between elemental distributions and charge collection efficiency 16 . Philippe et al 17 demonstrated the depth-dependent distribution of Cs and Rb and the role of the distributions in mixed-cation RbCsMAFA perovskite with hard X-ray photoelectron spectroscopy (HAXPES).…”
Section: Introductionmentioning
confidence: 99%